2005
DOI: 10.1037/0894-4105.19.6.778
|View full text |Cite
|
Sign up to set email alerts
|

No, It Is Not Possible to Be Schizophrenic Yet Neuropsychologically Normal.

Abstract: Cognitive impairment is well documented in schizophrenia, though some reports have been interpreted to suggest that it is possible to have schizophrenia without neuropsychological impairment. The authors tested this by comparing the neuropsychological profiles of closely matched patients with schizophrenia and healthy comparison participants. Sixty-four patients with schizophrenia and 64 healthy comparison cases, matched to within 3 Full-Scale IQ points, were tested using the Wechsler Adult Intelligence Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 26 publications
9
91
0
4
Order By: Relevance
“…The performance of PIQ is significantly lower than VIQ, and the Processing Speed is the lowest of 4 indexes. The results are consistent with the past findings [9,[14][15][16][17][24][25][26][27].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The performance of PIQ is significantly lower than VIQ, and the Processing Speed is the lowest of 4 indexes. The results are consistent with the past findings [9,[14][15][16][17][24][25][26][27].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the mean scores of patients in the Verbal Comprehension and Perceptual Organization indexes were higher than the Working Memory and Processing Speed. Wilk, et al also found that patients with schizophrenia were better than controls on Verbal Comprehension and Perceptual Organization but worse on Working Memory and Processing Speed [24]. Those findings indicated that patients with schizophrenia are impaired in cognitive functions: In the IQ scores, FSIQ was lower than expected, and PIQ was significantly lower than VIQ; in the index scores, the scores from high to low were Verbal Comprehension, Perceptual Organization, Working Memory, and then Processing Speed.…”
Section: Introductionmentioning
confidence: 88%
“…Reading abilities are also widely used in order to infer premorbid IQ in psychosis, as related to measures of full scale IQ, verbal IQ, verbal comprehension (Hanks et al, 2008) and verbal memory (Whitney et al, 2010), the latter being more impaired than general IQ at first episode of psychosis (Mesholam-Gately et al, 2009). This discrepancy between verbal and non-verbal scores in psychotic patients (Wilk et al, 2005) has been shown in people with a genetic liability to develop schizophrenia (Kravariti et al, 2006).…”
Section: Iq Assessmentmentioning
confidence: 71%
“…However, they support the notion that briefer test batteries are capable of providing researchers with almost as much information as longer batteries for calculating an overall composite score. As they reduce the time and resources required to conduct an assessment of neurocognition, they may be preferred over longer batteries for the calculation of summary scores in clinical trials (Wilk et al, 2005;Keefe et al, 2004;Velligan et al, 2004). However, brief approaches to the assessment of neurocognition may be more limited in their ability to provide information about specific neurocognitive effects of treatment, which will require more detailed assessment across multiple neurocognitive domains, as recommended in the conclusions of the MATRICS consensus process (Green et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%